2015
DOI: 10.2196/jmir.3637
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Traffic and Visitors’ Preferences Regarding Online Public Reports of Quality: Web Analytics and Online Survey Results

Abstract: BackgroundIn the context of the Affordable Care Act, there is extensive emphasis on making provider quality transparent and publicly available. Online public reports of quality exist, but little is known about how visitors find reports or about their purpose in visiting.ObjectiveTo address this gap, we gathered website analytics data from a national group of online public reports of hospital or physician quality and surveyed real-time visitors to those websites.MethodsWebsites were recruited from a national gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
(31 reference statements)
2
29
0
Order By: Relevance
“…The message explained the objectives and purpose of the study, and also included an invitation for recipients to complete an online questionnaire, following a link located in the body of the message. While online questionnaires are known for achieving modest responses (Bardach et al, 2015), the online option was chosen in view of various limitations, such as lack of resources to travel and visit different craft brewers individually, make long-distance telephone calls, or email paper questionnaires by mail. However, researchers (Tang, Amran, & Goh 2014) also report modest response rates using questionnaires sent by post and email.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The message explained the objectives and purpose of the study, and also included an invitation for recipients to complete an online questionnaire, following a link located in the body of the message. While online questionnaires are known for achieving modest responses (Bardach et al, 2015), the online option was chosen in view of various limitations, such as lack of resources to travel and visit different craft brewers individually, make long-distance telephone calls, or email paper questionnaires by mail. However, researchers (Tang, Amran, & Goh 2014) also report modest response rates using questionnaires sent by post and email.…”
Section: Methodsmentioning
confidence: 99%
“…First, despite complementing the data collection process with face-to-face and telephone interviews, which proved very useful for this first comparative study across countries, the overall number of participants is limited, and does not allow for making generalizations about the craft brewing industry or CBT. While online data collection can often produce low response rates (Bardach et al, 2015), given some of the challenges faced in this study, future cross-regional or cross-country research could follow a similar approach, complementing and enriching the data with short face-to-face interviews. Second, while the study had an international focus, more countries could have been targeted; future investigations could consider this alternative.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Given existing budget constraints the latter two alternatives were ruled out, and while there is evidence of various limitations of online questionnaire data gathering (Bardach, Hibbard, Greaves, and Dudley, 2015;Manfreda et al, 2008;Shih and Fan, 2008), this medium was chosen. Earlier wine business research has also adopted this data collection method (e.g., Johnson and Bruwer, 2007;McCutcheon, Bruwer and Li, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, studies suggest that consumers do not seek out this information, understand it, trust it, or know how to use it [7,8]. Promising strategies to increase consumer engagement in public reports are to improve the design [9,10], include patient narrative [11-14], and to tailor metrics to reflect the concerns and preferences of individual consumers [15]. It has been shown that the absence of tailoring in public reports makes them unlikely to succeed [16,17] and that consumers are deterred by the content and design of current reports that lack tailoring to their individual needs [18].…”
Section: Introductionmentioning
confidence: 99%